2018
DOI: 10.22159/ijap.2017.v9s2.23
|View full text |Cite
|
Sign up to set email alerts
|

Association Between the Degree of Gingival Inflammation and 25-Hydroxy Vitamin D Status in Postmenopausal Women

Abstract: Conclusion:There is no association between the degree of gingival inflammation and the 25(OH)D status among postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…For decades, researchers have discovered that activated analogues of vitamin D and vitamin D used as ointments can reduce or eliminate psoriasis and increase the effectiveness of ultraviolet light therapy. A recent study of 2018 observed no association between gingival inflammation and 25(OH) D status among the postmenopausal women [59].…”
Section: Inflammatory and Autoimmune Diseasesmentioning
confidence: 91%
“…For decades, researchers have discovered that activated analogues of vitamin D and vitamin D used as ointments can reduce or eliminate psoriasis and increase the effectiveness of ultraviolet light therapy. A recent study of 2018 observed no association between gingival inflammation and 25(OH) D status among the postmenopausal women [59].…”
Section: Inflammatory and Autoimmune Diseasesmentioning
confidence: 91%